2001
DOI: 10.1081/erc-100107864
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender and Diabetes on Vascular and Myocardial Contractile Function

Abstract: Premenopausal women have a lower cardiovascular risk than men or postmenopausal women. However, this "female advantage" is lost in diabetes, a condition characterized by cardiac and vascular contractile dysfunction. This study was designed to compare the influence of diabetes on vascular and myocardial contractile function between genders. Adult male and female rats were made diabetic with streptozotocin (55 mg/kg) and maintained for 8 weeks. Tension development was examined in thoracic aortic rings and left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
20
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
8
20
0
2
Order By: Relevance
“…However, we observed that endothelium-independent relaxation to SNP, an indicator of smooth muscle sensitivity to NO, was also clearly impaired 8 wk after the STZ injection in both sexes. This finding is in agreement with that of other investigators who also reported an impaired SNP-induced relaxation in diabetes (10,15). These data suggest that the responsiveness of vascular smooth muscle to NO is affected by STZ injection after 8 wk in both sexes.…”
Section: Vs C)supporting
confidence: 94%
“…However, we observed that endothelium-independent relaxation to SNP, an indicator of smooth muscle sensitivity to NO, was also clearly impaired 8 wk after the STZ injection in both sexes. This finding is in agreement with that of other investigators who also reported an impaired SNP-induced relaxation in diabetes (10,15). These data suggest that the responsiveness of vascular smooth muscle to NO is affected by STZ injection after 8 wk in both sexes.…”
Section: Vs C)supporting
confidence: 94%
“…This is consistent with our previous studies using multicellular papillary muscles and ventricular myocytes from chemically-induced diabetic rats (4,8). The reduced maximum velocity of shortening and relengthening associated with prolonged duration of shortening and relengthening may be resulted from the myosin heavy chain isoenzyme shift from V 1 to V 3 in diabetes (18).…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with our previous study on ventricular papillary muscles (8), diabetes ablated the gender-specific difference in myocardial function. There was no significant difference in contraction or relaxation parameters between the two genders under diabetic state.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This implies that diabetes is detrimental to cardiomyocytes, independent of macrovascular complications. Results from chemically induced insulinopenic (2) and genetically predisposed insulin-resistant (3) rodent models (4) as well as human histological (5) and clinical observations (6) provide support for this concept of a specific diabetic cardiomyopathy.…”
mentioning
confidence: 98%